Lithocarpus kamengii, a New Species from Arunachal Pradesh - Sahni, K. C.; Naithani, H. B. (Indian Forester, 1980)
A species of Lithocarpus new to science Lithocarpus kamengii Sahni & Naithani from Kameng District, Arunachal Pradesh, India, is described. This species is allied to Lithocargus milroyi (Purkayastha) Barnett but differs in having large leaves. 30-33 X 11-13 cm, Lateral nerves 18-pairs, cupule aggregated but 2.6 X 3 cm. This taxon is named after Kameng District from where it was recently collected.